Aplicación de la tomografía axial computarizada para la detección de bolsas de humedad en madera seca de gmelina arborea (roxb.) - Moya, Róger; Muñoz A., Freddy; Escalante, Iván (Revista de Ciencia y Tecnología, 2009)
Due to its excellent growth rate and productivity, Gmelina arborea (Roxb.) is widely used for commercial reforestation in Costa Rica. However during the lumber drying process, the wooden boards show non-uniform values of final moisture content (MC). The low uniformity in final MC is caused by the presence of "wet pockets", originated during the growing process of the tree. During the wood drying process, the regions with wet pockets present zones with a high MC, which are hard to detect with traditional methods for MC measurements. This article shows that it is possible to detect and to set the limits of the presence of wet wood in Gmelina arborea boards using scanning computed tomography (CT-scanning), a technique applied in medical diagnostic.